2008
DOI: 10.1007/s00421-008-0677-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of passive heating and head cooling on perception, cardiovascular function and cognitive performance in the heat

Abstract: The present study examined the effects of raising both skin temperature and core temperature, separately and in combination, on perceptions of heat-related fatigue (alertness, contentment, calmness and thermal comfort), cardiovascular function and on objective measures of cognitive performance (reaction time and accuracy). Ten (six males) subjects had cognitive performance assessed in three conditions; at low skin and low core temperature (LL), at high skin and low core temperature (HL) and at high skin and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 28 publications
5
84
3
Order By: Relevance
“…A hypothetical report suggested that increasing brain temperature could be therapeutic for depressive conditions (Salerian et al 2008). Conversely, Simmons et al (2008) reported that elevations in core temperature hindered cognitive function and worsened thermal fatigue (i.e., alertness, contentment, calmness, and thermal comfort). Thus, the literature is unclear regarding how a manipulation of body temperature might influence perception.…”
Section: Exercisementioning
confidence: 97%
“…A hypothetical report suggested that increasing brain temperature could be therapeutic for depressive conditions (Salerian et al 2008). Conversely, Simmons et al (2008) reported that elevations in core temperature hindered cognitive function and worsened thermal fatigue (i.e., alertness, contentment, calmness, and thermal comfort). Thus, the literature is unclear regarding how a manipulation of body temperature might influence perception.…”
Section: Exercisementioning
confidence: 97%
“…Various aspects of attention (19,22,65), memory (6,19,28,41,54), and executive function (16,17,67) are reduced in heat-stressed younger adults. Therefore, our findings that passive heat stress did not affect the measured indices of cognitive function are unexpected (Figs.…”
Section: Elevations In Body Temperature and Cognitive Functionmentioning
confidence: 99%
“…This chronological cognitive decline may contribute to the risk of deleterious outcomes during heat waves in older adults by, for instance, leading to poor decision-making. Interestingly, perhaps because of the deleterious impact of heat stress on cerebral blood flow (46,61) and/or disruptions in cerebral functional connectivity (66), many cognitive processes are impaired in heat-stressed younger adults [e.g., aspects of attention (19,22,65), memory (6,19,28,41,54), and executive function (16,17,67)], although this is not always observed (3,50,61). If heat stress-induced impairments in cognitive function are amplified with age, this might suggest that the contribution of cognitive factors to the risk of morbidity and mortality during heat waves would be exacerbated in older adults.…”
mentioning
confidence: 99%
“…Head cooling has been used for headache, 80 epilepsy, 81 multiple sclerosis, 82 sudden deafness from ischaemia of the inner ear, 83 and to alleviate environmental, occupational and exertional heat strain. 84,85 A more common use of head cooling is to cool the scalp to reduce hair loss with certain types of chemotherapy. 71,86,87 There are several commercially available scalpcooling devices.…”
Section: Other Applications Of Therapeutic Head Coolingmentioning
confidence: 99%